2001
DOI: 10.2134/agronj2001.1249
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Annual Medic Species (Medicago spp.) in Southeastern Wyoming

Abstract: Annual medic (Medicago spp.) pastures that produce high levels of good quality forage are well suited to grazing and are used extensively throughout dryland farming regions of the world. In these regions, they are normally an integral component of cropping rotations because they allow for reductions in weed and disease problems in addition to increasing soil N levels for subsequent crops. The objective of this research was to investigate the performance of 17 annual medic cultivars and experimental lines for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 10 publications
(18 reference statements)
3
45
2
Order By: Relevance
“…Medic nutritive values (CP, ADF, and NDF) were considered very high quality, and excellent for all classes of livestock (1). Crude protein values ranged from 17 to 22%, ADF ranged from 23 to 33%, and NDF values ranged from 28 to 41% (Table 2), which are similar to other medics(11,16) and alfalfa ( Medicago sativa L.) (7) nutritive values reported. Nutritive value did not differ between button, rigid, and Tifton burr medic species.…”
Section: Nutritive Valuesupporting
confidence: 77%
See 1 more Smart Citation
“…Medic nutritive values (CP, ADF, and NDF) were considered very high quality, and excellent for all classes of livestock (1). Crude protein values ranged from 17 to 22%, ADF ranged from 23 to 33%, and NDF values ranged from 28 to 41% (Table 2), which are similar to other medics(11,16) and alfalfa ( Medicago sativa L.) (7) nutritive values reported. Nutritive value did not differ between button, rigid, and Tifton burr medic species.…”
Section: Nutritive Valuesupporting
confidence: 77%
“…Annual medics are cool‐season forage legumes that have potential in the southern Great Plains of the United States since they are typically better adapted to harsh environmental conditions (16) and high soil pH compared to other cool‐season annual legumes. Annual medics can produce high quality forage (11,13,16) that is beneficial to livestock producers, as well as aiding in the restoration of soil fertility of arable soils(5,16). They have the potential to increase forage production and extend the grazing season, while reducing the need for nitrogen fertilizer.…”
Section: Potential Of Annual Medicsmentioning
confidence: 99%
“…Screening of self-regenerating legumes for local adaptation in central Manitoba , Wyoming (Walsh et al 2001), and Minnesota (De Haan et al 2002) has failed to identify a particular species or genotype that would satisfy all the requirements of a self-regenerating cover crop system, but has indicated that desirable characteristics were present in the screened germplasm and that these qualities could be further developed.…”
Section: Cover Cropsmentioning
confidence: 99%
“…The trial was established on April 23. All eight cultivars were sown at a density of about 250 viable seeds m -2 (Walsh et al 2001), a plot size of 1 m 2 , three replicates for forage production and one plot for seed production, a row spacing of 20 cm both within and between plots in order to reduce excessive growth of border rows of a plot. In fact, each cultivar was sown in seven rows, but only fi ve inside the plot were taken into account, while two border rows were discarded.…”
Section: Introductionmentioning
confidence: 99%